Preimplantation genetic testing for a family with usher syndrome through targeted sequencing and haplotype analysis - Haining Luo; Chao Chen; Yun Yang; Yinfeng Zhang; Yuan Yuan; Wanyang Wang; Renhua Wu; Zhiyu Peng; Ying Han; Lu Jiang; Ruqiang Yao; Xiaoying An; et al. (BMC, 2019)
Abstract Background Preimplantation genetic testing for monogenic defects (PGT-M) has been available in clinical practice. This study aimed to validate the applicability of targeted capture sequencing in developing personalized PGT-M assay. Methods One couple at risk of transmitting Usher Syndrome to their offspring was recruited to this study. Customized capture probe targeted at USH2A gene and 350 kb flanking region were designed for PGT-M. Eleven blastocysts were biopsied and amplified by using multiple displacement amplification (MDA) and capture sequencing. A hidden Markov model (HMM) assisted haplotype analysis was performed to deduce embryo's genotype by using single nucleotide polymorphisms (SNPs) identified in each sample. The embryo without paternal rare variant was implanted and validated by conventional prenatal or postnatal diagnostic means. Results Four embryos were diagnosed as free of father's rare variant, two were transferred and one achieved a successful pregnancy. The fetal genotype was confirmed by Sanger sequencing of fetal genomic DNA obtained by amniocentesis. The PGT-M and prenatal diagnosis results were further confirmed by the molecular diagnosis of the baby's genomic DNA sample. The auditory test showed that the hearing was normal. Conclusions Targeted capture sequencing is an effective and convenient strategy to develop customized PGT-M assay.